Optimal control for soft-landing in elevator emergency crash using multiple magnetorheological shock absorbers. (November 2022) - Zheng, Jiajia; Zhao, Jiajiang; Wang, Linlin; Li, Zhaochun; Dong, Weiping; E, Shiju
Protecting the occupants from surviving the casualties and severe injuries in elevator emergency crashes is always essential. This paper aims to explore the feasibility of using multiple magnetorheological shock absorbers (M-MRSAs) to attain the soft landing of a full-load elevator under impact velocities ranging up to 32 m/s. The resistance forces of MRSA with a bi-fold structure are predicted by evaluating the pressure drops using a nonlinear Bingham-plastic model considering the effects of minor loss. The optimal control for an M-MRSAs system achieving robustness concerning different mass loadings and impact velocities is investigated by formulating a multi-objective problem to minimize the induced peak acceleration with constrained time duration. The results demonstrate that the self-adapting MR yield force provides a smooth operation by minimizing the cycles of re-crash and rebound without incurring an end-stop impact. Furthermore, a plateau behavior of acceleration-displacement profiles is realized to effectively reduce the load transmission from overshoot accelerating force to the protected occupants and eliminate the injury risk.